Fungsi, Kategori, dan Peran Sintaksis Dalam Talk Show One “Indonesia Lawyers Club” di TV One - Susandhika, I Gusti Ngurah Mayun; Darma Laksana, I Ketut; Suparwa, I Nyoman (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 23 (2016): March 2016)
This study aims to understand the syntactic function of the function, category, and tree diagram in the talk show one “Indonesia Lawyer Club” on TV ONE. This study uses the theory of RRG (Role and Reference Grammar) proposed by Robert D. Van Valin, Jr. and Randy J. LaPolla (1997). This research data is in the form of sentences in Indonesian language. The data was collected using refer method and note technic. The main method that was used to analyze data was distributional method, while the application of this method was assisted with based technique, direct element distributional technique. The result is presented using formal and informal method with inductive and deduktive technique. The result are the syntactic functions contain subject, predicate (core) or nucleus, and objects, the category of subject and object is a noun, while the predicate (nucleus) is a verb and an adjective, and the subject's role is as an actor, the object as a patient, and the predicate (nucleus) describes the activities or circumstances. Nucleus or the core of the sentence is on the right. Besides, it was also found the result in the form of tree structure or tree diagram in its category.
Keywords: syntax, function, category, role, and tree diagram